The Linkage of Students’ Synchronous and Autonomous Learning at the Tertiary Level - Khulaifiyah Khulaifiyah; Sri Yuliani; Fara Azzahra Aulia (AL-ISHLAH: Jurnal Pendidikan, 2023)
The goal of the research is to find out whether students’ synchronous learning correlates highly to their autonomous learning. Knowing that activities during synchronous learning must standardized into certain syllabus so that, learning process can be imitated into asynchronous learning nowadays. Therefore, studying the topic is still needed. This study used quantitative data that researchers obtained from numerous respondents. 100 participants, dominantly English Language Education students who experienced synchronous learning, already became active respondent to this study. A questionnaire comprised 15 items about how intensive students know the objective, specific or personal goal, negotiation, additional learning resources, checking their achievement and others during synchronous learning. The research applied a sequential exploration design in which quantitative data is collected and analyzed using SPSS 23. The result reveals that the sig value is 0.030 bigger () than 0.05. Thus, it shows a significant difference between the value of the synchronous relationship and autonomous learning when compared to the standards set. Next, it is reviewed further that the t value shows a positive score, meaning the research acquisition value is higher than the specified score. Synchronous learning has upgraded students’ autonomous learning.  Therefore, from the results of the test, it can be concluded that there is a high correlation between synchronous and students' autonomous learning.